Орієнтовна вартість і тривалість комплексів робіт у житловому будівництві - Алтухова, Д. В.; Зельцер, Р. Я. (Ways to Improve Construction Efficiency, 2014)
Article provides information of the elaboration of indexes of estimated cost and duration of the enlarged complexes of works for the frame-monolithic multistoried residential buildings. Figures were differentiated depending on the number of floors. They are designed for use during devising bar diagrams and graphs on the phase of the project of organization of construction.